A study of the structure-affinity relationship in SYA16263; is a D2 receptor interaction essential for inhibition of apormorphine-induced climbing behavior in mice?. (15th January 2021) - Onyameh, Edem K.; Bricker, Barbara A.; Eyunni, Suresh V.K.; Voshavar, Chandrashekhar; Gonela, Uma M.; Ofori, Edward; Jenkins, Andrea; Ablordeppey, Seth Y.
Graphical abstract: Abstract: Dopamine (DA) and serotonin (5-HT) receptors are prime targets for the development of antipsychotics. The specific role of each receptor subtype to the pharmacological effects of antipsychotic drugs remains unclear. Understanding the relationship between antipsychotic drugs and their binding affinities at DA and 5-HT receptor subtypes is very important for antipsychotic drug discovery and could lead to new drugs with enhanced efficacies. We have previously disclosed SYA16263 (5 ) as an interesting compound with moderate radioligand binding affinity at the D2 & D3 receptors ( Ki = 124 nM & 86 nM respectively) and high binding affinities towards D4 and 5-HT1A receptors ( Ki = 3.5 nM & 1.1 nM respectively). Furthermore, we have demonstrated SYA16263 (5 ) is functionally selective and produces antipsychotic-like behavior but without inducing catalepsy in rats. Based on its pharmacological profile, we selected SYA16263 (5 ) to study its structure-affinity relationship with a view to obtaining new analogs that display receptor subtype selectivity. In this study, we present the synthesis of structurally modified SYA16263 (5 ) analogs and their receptor binding affinities at the DA and 5-HT receptor subtypes associated with antipsychotic action. Furthermore, we have identified compound 21 with no significant binding affinity at the D2 receptor subtype but with moderate binding affinity at the D3 and D4 receptors subtypes. However, because 21 is able to demonstrate antipsychotic-like activity in a preliminary test, using the reversal of apomorphine-induced climbing behavior experiment in mice with SYA16263 and haloperidol as positive controls, we question the essential need of the D2 receptor subtype in reversing apomorphine-induced climbing behavior.